2022
DOI: 10.3389/fpubh.2022.1038211
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prediction model of patients with carcinosarcoma in the United States

Abstract: BackgroundCarcinosarcoma is a rare biphasic tumor composed of both carcinoma and sarcoma elements, which occurs at various sites. Most studies are case reports or small population-based studies for a single disease site, so comprehensive evaluations of epidemiology and prognostic factors for carcinosarcoma are needed.MethodsSurveillance, Epidemiology, and End Results (SEER)-8 (1975–2019) provided data for the epidemiological analysis. SEER-17 (2000–2019) provided data on the primary tumor sites, initial treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Recently, Chen et al [2] in their multivariate analysis showed that age, race, year of diagnosis, FIGO stage, and treatment type can also be associated with survival and formed a similar nomogram with a good predictive capacity. Another study formed a nomogram predicting the overall survival of patients with ovarian carcinosarcoma including the following parameters: age, grade, tumor site, surgery, and chemotherapy [3].…”
mentioning
confidence: 99%
“…Recently, Chen et al [2] in their multivariate analysis showed that age, race, year of diagnosis, FIGO stage, and treatment type can also be associated with survival and formed a similar nomogram with a good predictive capacity. Another study formed a nomogram predicting the overall survival of patients with ovarian carcinosarcoma including the following parameters: age, grade, tumor site, surgery, and chemotherapy [3].…”
mentioning
confidence: 99%